The Effect of Mangosteen Peel Extract (Garcia Mangostana L) and Shelf Life on the Physical Quality of Chicken Eggs - Rukmini, Ni Ketut Sri; Suwitari, Ni Ketut Etty; Rejeki, I Gusti Ayu Dewi Seri (International Journal of Contemporary Sciences (IJCS), 2024)
This study investigates the effect of mangosteen peel extract immersion on the quality of broiler chicken eggs during storage. Mangosteen peel (Garcinia mangostana L) contains bioactive compounds, such as xanthones, with antioxidant properties that can protect cells from oxidative damage, including egg cells. The research employed a completely randomized design with two factors: different concentrations of mangosteen peel extract (0%, 5%, 10%, and 15%) and storage durations (0, 1, 2, 3, and 4 weeks). Data were analyzed using ANOVA, followed by the Duncan test for significant results (P < 0.05). The findings revealed a highly significant effect (P < 0.01) of mangosteen peel extract on egg quality, measured through pH, egg white index, egg yolk index, and Haugh unit. Notably, eggs soaked in 10% mangosteen peel extract for 24 hours showed the highest Haugh unit value after 4 weeks of storage. The study suggests that tannins in the extract prevent egg white dilution, effectively preserving egg quality during storage.